PENGARUH KEMAMPUAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PANTI SOSIAL ASUHAN ANAK TUNAS BANGSA PATI - Adhana, Romansyah arindra; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2016)
Social problems is one big thing in Indonesia that must be dealt with quickly and appropriately. Ministry of Social Affairs is the ministry that handles this problem by creating the Technical Implementation Unit to resolve the social problems that exist in the districk. Social Homes Children Care Tunas Bangsa Starch is one of UPT is responsible for dealing with social problems such as educating disadvantaged children and the displaced as well as do some other social services in Pati Districk. The purpose of this study is to identify and analyze the performance, Skill, and work discipline toward employees performance and to determine the effect of the ability and discipline to employee performance PSAA Tunas Bangsa Pati. This study uses a quantitative explanatory research design with respondents from employees PSAA Tunas Bangsa Pati. The process begins by determining the number of samples of all employees PSAA Tunas Bangsa Pati. Using a questionnaire so we get an answer from each variable. With the effects of the ability and discipline toward employees performance PSAA Tunas Bangsa Pati using correlation formula Kendal Tau, Tau, concordance Kendal, and coefficient determinan there are significant determinant of the ability and discipline toward performance of employees. Based on the results of correlation Kendal Tau, a significant difference between the ability and discipline to the performance of employees. The need for improvements to improve employee performance.